On Love, Coercion, Violence, and Democracy - Norkus, Zenonas (Problemos, 2006)
The paper discusses the implications of two hypotheses prominent in the contemporary literature in the fields of comparative politics and international relations: (1) the democratic peace hypothesis; (2) the hypothesis of the superior military effectiveness of democracies. The author maintains that the conjunction of these hypotheses implies that democracies are bound to expand and oust non-democracies, because democracies do not go to war with other democracies (but do that with non-democracies), and because, under present conditions of war technology, democracies win over non-democracies. This argument provides explanation of the recent world-wide trend of democratization and stands logically on its own with respect to other influential explanations of this phenomenon. The paper is introduced by the conceptual analysis discussing relations among the concepts of coercion, violence and democracy, where the thesis is substantiated that community of love is the only form of social life that is thinkable as involving no coercion, no violence, and therefore also no democracy. However, such community is viable only as an island in a broader society whose members suspect that members of the community of love are coerced into it by means of brainwashing.
Keywords: love; coercion; violence; democratic peace hypothesis; military effectiveness of democracy